The Failure of Philosophical Love: A Reading on Plato’s Symposium - Franco, Irley F. (Revista Archai, 2018)
In this paper I argue that Socrates’ speech in Plato’s Symposium cannot by itself express Plato’s view of love. All the non-philosophical speeches, each standing for a different contemporary view of love, should be taken into serious consideration, for they are not mere pastiches of empty theories. In fact, they seem to have been placed there to have their intellectual strength tested by philosophy, for not only their contents reveal commonsensical accepted wisdom, but their discursive beauty powerfully impresses the audience, making them true challenges to the cold, though persuasive logos of philosophy. Furthermore, placing Alcibiades’ speech right after Diotima’s austere account of love, when the program of speeches as proposed seemed to have arrived at an end, would be unnecessary, if Plato’s aim were simply to disapprove Alcibiades’ behavior to excuse Socrates political attitudes, as it is assumed by Leon Robin in his Notice to his famous translation to the Belles Lettres edition. On the contrary, Alcibiades’ speech sounds more like a criticism of Socratic love made by Plato himself.